Innovative Sodium Cleaning Process Using Saline Solutions - Leïla Gicquel; Sébastien Lefèvre; Laure Moinot; Benjamin Tardivel (Chemical Engineering Transactions)
During the development of NOAH process at CEA in the 1980s (Rodriguez, 2021), the addition of sodium hydroxide to water was identified as an interesting way to moderate the kinetics of the sodium-water reaction. Based on these observations, studies were launched at CEA in 2007 with the aim of developing an innovative process for treating remaining sodium in the components of a sodium fast reactor (SFR). This process would have the following advantages: control of the sodium-water reaction and limitation of its effects by adding an appropriate salt; flexibility and increase in treatment rates by rapid immersion of the components. In order to overcome the corrosive nature of sodium hydroxide, new salts were studied. Several salts appeared promising in that, for some of them, the reaction no longer generates a shock wave despite an excess of water, the kinetics are slowed down and the release of energy occurs gradually in the reaction medium. Following these results, new experimental campaigns were launched and enabled to identify the influential parameters and to quantify the effects of two salts on the moderation of the sodium-water reaction: tetrasodium EDTA and sodium acetate.